Evaluation of Control Program Against Streptococcus agalactiae Infection in Dairy Herds During 2019–2021 in Emilia-Romagna Region, Northern Italy - Tamba, Marco; Rocca, Rossella; Prosperi, Alice; Pupillo, Giovanni; Bassi, Patrizia; Galletti, Giorgio; Martini, Enrica; Santi, Annalisa; Casadei, Gabriele; Arrigoni, Norma (Frontiers in Veterinary Science, 2022)
Streptococcus agalactiae (group B Streptococcus, GBS) is a causative agent of mastitis in dairy cattle, mainly causing a subclinical disease associated with a high Somatic Cell Count (SCC), and a consequent decrease in production yield and quality of milk. GBS has been almost eradicated in many Northern European Countries, but there are warnings of its re-emergence as a zoonosis. In Italy, only two regions carry out a GBS control program: Lombardy and Emilia-Romagna. In Emilia-Romagna the program is in place since 2019 and provides for the bacteriological culture of bulk-tank milk (BTM) of all dairy farms every six months and the voluntary application of herd eradication programs in case of positive results. In order to assess the progresses of the program in Emilia Romagna, in terms of herd-level prevalence and GBS transmission between herds, we analyzed the results of 17,056 BTM cultures from 2,831 dairy herds, sampled bi-annually in the period 2019-2021 (six rounds total). The impact of GBS infection on SCC and milk production was also evaluated. The results show a decreasing trend in both the incidence rate (from 3.0% to 1.5%) and apparent prevalence (from 8.9% to 5.2%) of GBS over the study period. By using a Susceptible-Infected-Susceptible (SIS) model for the estimation of the transmission parameters, a basic reproductive number R0 of 1.4 was calculated, indicating an active spread of GBS in the dairy cattle population of the Emilia-Romagna region. GBS infected farms have a consistently higher BTM SCC than negative ones (+77,000 cells/mL), corresponding to a 0.4 Kg/cow/day milk loss. Moreover GBS infected herds resulted almost three times more likely to have a non-marketable milk by exceeding the legal SCC limit. This study demonstrates the need to maintain the current control program against GBS in order to lower its occurrence and prevent significant market losses to the farmers.